Please show all work.
3 cos x + 3 = 2 sin^2 x3 cos x +3 = 2( 1- cos^2 x)3 cos x + 3 = 2 - 2 cos^2x2cos^2 x+3 cos x +1 = 02 cos^2 + 2 cos x + cos x + 1 = 02cos x ( cos x +1)+1 (cos x+1) = 0(2cos x +1)(cos x + 1) =0therefore,2cos x + 1 = 0 and cos x+1 = 0so, 2cos x=-1 and cos x =-1cos x = -1/2 and cos x =-1hence,x = cos^-1 (-1/2) and x = cos^-1 (-1)x = 2pi/3 and x = piPlease appreciate my help by selecting my answer as the best, Thanks! :)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?